Theory of Operation of a Safety Finger Coupling Applied in the Drive of a Screw Conveyor for Bulk Agricultural Materials - Bulgakov, Volodymyr (2024)
The aim of the study is to enhance the operational characteristics of a screw conveyor during overloading of its working mechanism by substantiating the rational parameters of the safety coupling. Theoretical calculations and their graphical dependencies were performed using the Delphi programming environment. To increase the magnitude of axial displacement of the driven half-coupling with the jammedworking element, while reducing dynamic loads during overloading, a design of a safety coupling has been developed. To determine the rational parameters of the safety coupling for the screw conveyor, the influence of dynamic loads on the operation of the safety coupling during overloading of the screw conveyor’s working mechanism has been analyzed. From the analysis of the graphs, it has been determined that an increase in the rotation frequency n leads to an increase in the torque of the system. With a change in rotation frequency from 50 rpm to 200 rpm, the torque Td increases by 64.8%, Tr rises by 65.2%, and Tm increases by 63.8%. It has also been determined that an increase in the mass m of moving links leads to an increase in loads on the drive. When the mass increases from 10 kg to 20 kg, the torque Td increases by 15.8%, Tr rises by 12.5%, and Tm increases by 17.3%.